Immunoinflammatory evidence of rheumatoid arthritis caused by COVID-19 - Zhiqiang Shao; Dan Xia; Liang Zhou; Zonghan Xu; Jiaqian Wang (Biological Research)
Abstract Purpose The relationship between coronavirus disease 2019 (COVID-19) and rheumatoid arthritis (RA) remains uncertain. We aimed to assess the association between COVID-19 and RA through immune inflammation. Methods First, we conducted a meta-analysis on the risk of COVID-19 infection, hospitalization rate, and mortality rate for patients with RA. Then, Mendelian randomization (MR) was used to evaluate the causal relationship between COVID-19 and RA, and further analyzed the cytokines and immune cells in COVID-19 and RA. Finally, we obtained microarray datasets of COVID-19, RA patients, and normal controls from the GEO database. And performed functional, pathway enrichment, and immune cell infiltration analysis on differentially expressed genes between each group. Results The meta-analysis results suggested that the hospitalization rate and mortality rate of RA patients infected with COVID-19 were higher than those of the control population. MR analysis showed a positive correlation between COVID-19 infection and RA. We also found that interleukin 13 was associated with RA and COVID-19 infection. CD27 on IgD + CD24 + B cells and CD3 on CD39 + CD8 + T cells are common immune cell phenotypes in two diseases. In addition, COVID-19 function is enriched in immune responses mediated by leukocytes and neutrophils, while RA is significantly enriched in the proliferation of T and B lymphocytes. The results of immune cell infiltration showed that both diseases had more neutrophils and fewer CD8 T cells. Conclusion There are many similarities between COVID-19 and RA in immune inflammatory responses such as cytokines and immune cells. COVID-19 may lead to the development of RA through immune inflammation.